Johann Friedrich August von Esmarch – the Father of First Aid surgery (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Regarded as the Father of  First Aid and surgical haemostasis for  the war wounded soldiers, Johann Friedrich August von Esmarch was one of the greatest military surgeons ever born. His contributions range from devising his own illustrated bandage to application of tourniquet to prevent  blood loss in trauma victims in the battlefield. He has also invented an inhalation mask for chloroform anesthesia, splints and surgical instruments. He changed the way the war wounds were managed and made many serious war injured victims go home aliveJ Bangladesh Coll Phys Surg 2023; 41: 244-247